Enzymatic hydrolysis of rapeseed oil with a non-GMO lipase: A strategy to substitute mono- and diglycerides of fatty acids and improve the softness of sponge cakes. (February 2021) - Monié, Aurélie; David, Annabelle; Clemens, Karine; Malet-Martino, Myriam; Balayssac, Stéphane; Perez, Emile; Franceschi, Sophie; Crepin, Martine; Delample, Mathieu
Abstract: Mono- and diglycerides of fatty acids (MDGs) are commonly used in the production of sponge cakes due to their ability to form inclusion complexes with amylose, which prevents staling. They are considered as food additives and have to be mentioned on the ingredient list. The aim of this study was to use an enzymatic strategy in order to generate in situ mono- and diglycerides of fatty acids, starting from rapeseed oil and a non-GMO lipase through emulsification. Reaction products were first characterized by Gas Chromatography (GC). Proton Nuclear Magnetic Resonance ( 1 H NMR) was employed as an additional technique to qualify and selectively identify the monoglyceride isomers. After 2 h of lipolysis, a high amount of MDGs was reached. Beyond this point, a continuous decrease was observed until 24 h. When used in total substitution of rapeseed oil, modified oils (2 h or 24 h) impact negatively the structure of cakes and have to be diluted before use. The structure and the softness of the products were characterized and followed up to 6 months. The best results were obtained with a 24-h enzymatic reaction and by diluting between 5 and 25 g/100 g in unmodified rapeseed oil. Highlights: Selective mono & diglycerides enrichment of rapeseed oil was obtained by a lipase. Molecular profile of oils evolved as a function of the lipolysis time. Amounts of all reaction products were obtained by Gas Chromatography and 1 H NMR. Modified oils impact the structure of cakes and have to be diluted in rapeseed oil. The presence of modified oil improves the softness of cakes and prevents staling.